# FREE MAP HS Math Questions and Answers

0%

#### In the solution set of -5x – 25y < -30, which of the following ordered pairs is present?

Correct! Wrong!

The given inequality is -5x – 25y < -30.

Consider the point (6,0). Take this point and check the inequality as follows:

-5(6) – 25(0) < -30
-30 < -30

This is false. So, (6,0) cannot be the solution.

Consider the point (21,-3). Take this point and check the inequality as follows:

-5(21) – 25(-3) < -30
-105 + 75 < -30
-30 < -30
This is false. So, (21,-3) cannot be the solution.

Consider the point (4,-3). Take this point and check the inequality as follows:
-5(4) – 25(-3) < -30
55 < -30

This is false. So, (4,-3) cannot be the solution.

Consider the point (5,1). Take this point and check the inequality as follows:
-5(5) – 25(1) < -30
-50 < -30
This is true. So, (5,1) is the solution.

Correct! Wrong!

#### Which of the following inequality best characterizes the part's range and domain?

Correct! Wrong!

Remember that the function's domain includes all values that the x-axis line covers. The line on the graph spans the x-axis from -3 to 3..

So, the domain will be -3 ≤ x ≤ 3.

Additionally, keep in mind that the function's range includes any values that are covered by the y-axis line.
The line graph, as seen in the graph, spans the y-axis from -2 to 1..
Thus, the range of the function is -2 ≤ x ≤ 1.

#### Which of the following statements most accurately depicts the line's grid equation and its relationship to the y-axis?

Correct! Wrong!

The graph indicates that the specified line is perpendicular to the x-axis and parallel to the y-axis. Furthermore, the line that crosses the x-axis at x = -3.

So, the equation of the line is x = -3.

#### In a grocery store, a customer purchased 58 products for a total of \$4.20. Bananas made up the majority of the products, with some apples included. • Each apple costs \$0.05 • Each banana costs \$0.10 Which set of equations may be used to determine, from the customer's purchases at the grocery shop, a) the number of apples and b) the number of bananas?

Correct! Wrong!

There are a few apples and bananas among the 58 total items.

Represent this condition algebraically as follows:

a + b = 58

The buyer must next fulfill the remaining requirement, which is \$4.20. In this instance, an apple costs \$0.05 while a banana costs \$0.10.

SGiven that there are apples and that each one costs \$0.05, the outcome is \$0.05a.
Because there are b bananas and they each cost \$0.10, \$0.10b is the outcome.
Represent the above condition algebraically as follows:
0.05a + 0.10b = 4.20

#### What expression can be used in place of 64x2 – 225?

Correct! Wrong!

Make the expression simpler 64x² – 225

64x²– 225 = (8x)² – (15)²

Recall the identity (a + b)(a – b) = a² – b². So, a = 8x and b = 15.

Thus, (8x)² – (15)² = (8x – 15)(8x + 15).

#### Take a look at the function f(x) = x² – 9x + 20. Which of these claims about the following is true?

Correct! Wrong!

The given function is as follows:

f(x) = x² – 9x + 20

Factorize the given function as follows:

f(x) = x² – 9x + 20
f(x) = x² – 4x – 5x + 20
f(x) = x(x – 4) – 5(x – 4)
f(x) = (x – 4)(x – 5)

The factors are (x – 4) and (x – 5).
Now, find the zeros as follows:

(x – 4)(x – 5) = 0
Thus, the zeros are x = 4, and x = 5.

#### Which of the following expressions is 9x² + 72x + 144?

Correct! Wrong!

The given expression is 9x² + 72x + 144.

Recall the identity (a + b)² = a² + 2ab + b².

Write the expression in the identity form as follows:

9x² + 72x + 144 = (3x)² + 2 ∙ 3x ∙ 12 + (12)²

9x² + 72x + 144 = (3x + 12)²

#### What phrase can be used in place of √176?

Correct! Wrong!

Construct 176's prime factorization as follows:

176 = 2 × 2 × 2 × 2 × 11

Assign the prime factors in pairs:

176 = (2 × 2) × (2 × 2) × 11

Now, calculate both sides' positive square roots:

√176 = √((2 × 2) × (2 × 2) × 11)

√176 = 4√11

Therefore, √176 = 4√11.

#### Which of the following represents 6x² – 17x + 5 in factored form?

Correct! Wrong!

Examine the quadratic expression provided 6x² – 17x + 5.

Factorize the following expression:

6x² – 17x + 5 = 6x² – 15x – 2x + 5

6x² – 17x – 5 = 3x(2x – 5) – 1(2x – 5)

6x² – 17x – 5 = (2x – 5)(3x – 1)

Thus, the factored form is (2x – 5)(3x – 1).